Collaborative traffic density application - Vu, Phuong (2013)
Over the years, live traffic applications in mobile phone have been studied and developed. Live traffic applications provide users with constant, variety and continuous traffic situation in order to facilitate users while traveling. This project proposed a traffic application for iPhone mobile platform. The target location of this application is Singapore. In this report, the process of the development are captured in the form of diagrams, problem discussion, and screenshots. Feature and functionality of the iPhone application are presented. The implementations of server-side application as well as client-side application are discussed. User evaluation is used for analyzing the usability, performance and usefulness of the features in the system. The report would then be concluded with recommendations for improvement on the system.